Career paths : Finance - Evans, Virginia; Dooley, Jenny; Patel, Ketan C. (Newbury Express Publishing, 2018)
Career Paths Finance is a new educational resource for finance professionals who want to improve their English communication in a work environment.
Keywords: Tài chính Ngân hàng